Risk factors of the patellofemoral pain syndrome - Widhiantari, Ni Ketut Evitri; Widnyana, M.; Jawi, I Made (Kinetic and Physiotherapy Comprehensive, 2023)
Background: Patellofemoral pain syndrome (PFPS) is one of the common injuries to the knee that often occur, causing pain when doing physical activities such as squatting, running or going up and down stairs when the knee is bent. As the joint that supports the body the most, this certainly hinders a person's activities. PFPS is caused by various risk factors ranging from intrinsic factors such as muscle strength to extrinsic factors such as type of activity. This study aimed to determine the risk factors related to PFPS as a preventive effort by doing quadriceps muscle strengthening exercises.  Methods: This study used a literature review study design using secondary data from published literature. Literature searches were conducted online through PubMed, ScienceDirect, and Google Scholar, using the keywords “knee injury”, “patellofemoral pain”, “patellofemoral pain syndrome”, and “risk factors”, which selected based on inclusion and exclusion criteria. Results: From the five studies that discussed risk factors related to PFPS, it was found that all journals showed quadriceps muscle strength, type of daily activity, Q-angle, joint laxity, hip tightness, patellar imbalance, overuse, and patellofemoral joint overpressure were associated with PFPS. Conclusion: Based on the literature that has been reviewed and the discussion, the dominant risk factor associated with PFPS was a decrease in hip muscle strength, especially quadriceps. Besides, several other contributing factors include the type of daily activity, Q-angle, joint laxity, hip tightness, patellar imbalance, overuse, and patellofemoral joint overpressure.